Finite time stability of linear fractional order dynam-ical system with variable delays - P. C, Jackreece; S. E, Aniaku (International Journal of Applied Mathematical Research, 2018)
In this paper, some sufficient condition ensuring finite time stability are derived for a class of linear fractional order dynamical system with variable delay using generalized Gronwall inequality as well as classical Bellman-Gronwall inequality.